Qualitative research: Utilization of the mobile application of national health insurance (JKN) to increase the effectiveness of services - Eli Marlina Lubis; Nofi Susanti (Malahayati International Journal of Nursing and Health Science, 2023)
Background: Sundari General Hospital has implemented an online registration system as a solution to the problem of patient backlogs. Patient registration via the national health insurance mobile (M-JKN) application at Sundari General Hospital has yet to reach the set target.Purpose: To analyze patient registration through the national health insurance mobile application at Sundari General Hospital.Method: Qualitative research uses a case study approach. The research was conducted from April to July 2023. The informants in the study were 10 people. The research instrument uses a list of questions as an interview guide. The information-gathering process was carried out using in-depth interviews, observation and documentation.Results: Showed that the input component has been running well, but there are still some obstacles, such as training for officers, inadequate patient infrastructure, and socialization to patients. The patient registration process has been carried out according to the SOP, but there are still many patients who need help understanding the use of the M-JKN application. The output component needs to be optimized due to the low participation of patients who register through the M-JKN application.Conclusion: Patient registration via the national health insurance mobile application at Sundari General Hospital has been going well, although there are still obstacles, and utilization is still low. However, it has been quite effective in reducing the buildup of patient queues.